Analysis of the effect of international trade openness on inequality between districts/cities in Indonesia's provinces - Rahmi Fadhillah; Zamroni Zamroni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to determine the impact of international trade openness on regional inequality in Indonesia's provinces by using the concept of economic geography. Other factors such as geographic accessibility, labor share in the manufacturing sector, population, and government expenditure are also estimated. This study uses panel econometric analysis. The data used from 33 provinces in Indonesia from 2003-to 2018 was obtained from Statistic Indonesia (BPS). The result shows that international trade openness has a positive effect on increasing inequality between regions. However, openness to international trade hurts increasing inequality between regions if it is supported by geographic accessibility. The economic dispersion causes this due to cost efficiency and competitive forces. In addition, the share of labor in the manufacturing sector has no effect. However, the population and the government expenditure have a positive and significant effect on regional inequality. Positive exports tend to reduce regional inequality. Each province's exports and imports also affect this result.